Вы находитесь на странице: 1из 18

Oz

r < a

ε r r [a; b]

r > b

l c V I c 0 =

1

l.c

c

= 2πε 0 ε r
µ
b
0
c =
ln b
2π ln a
a
1
c l
c 0 =
.c
=
ε r

c l

1
Z c = .c 0 =
c =
c.c 0
1
c 0 =
√ .c Ω
 Z c 50Ω ˜ ˜ V + = Z c I + x ˜ ˜ V − = −Z c I − x

x I + x I

I (t, x)

=

I + t

x 0 + I t +

c

x

c

0

V (t, x) = Z c .I + t

x 0 Z c .I t +

c

x

c

0

.dx dE L = 1 2 .dx.I 2
e L =
1 .I 2
2
c.dx dE C = 1 2 c.dx.V 2
1
e C =
2 c.V 2
dx dE = dE L + dE C = 1 2 .dx.I 2 +
2 1 c.dx.V 2
1
e = e L + e C =
1 2 · I 2 + 2 c.V 2
 e L = e C ⇒ e = .I 2 = c.V 2 x < x 0 x > x 0 P(t) = V (x 0 , t).I(x 0 , t) x > x 0 x < x 0 x > x 0
∂e
= − ∂P
∂t
∂x

Z c x = x 0

˜

Z

˜
˜
I r (x = x 0 , t)
V r (x = x 0 , t)
r I =
r V =
˜
˜
I i (x = x 0 , t)
V i (x = x 0 , t)
P r
R =
∈ [0, 1]
P i
P =
1
2
˜
V
. I ˜

Z c

˜

Z

R =

2

Z Z c

2

R

˜

Z c + Z

˜

 ˜ Z = Z c

Z 1 x = x 0 Z 2

= V t (x = x 0 , t)
t I = I t (x = x 0 , t)
t V
I i (x = x 0 , t)
V i (x = x 0 , t)
P t
T =
⇒ R + T = 1
P i

 l c r 1 g 2 r 1 = 0 g 2 = 0 ψ( r, t) = ψ( r, t) ˜ ψ ˜ k x−ω t+ϕ 0) = ψ 0 .e j ( ˜ ˜ ψ 0 ϕ k ˜ k ω ˜ k = k r + j.k i k r = k ˜ k i = k ˜ ψ ˜ = ψ 0 .e −k i .x .e −j.(ω.t−k r .x−ϕ 0 ) x k i > 0

ψ ˜ = ψ 0 .e −k i .x .e −j.(ω.t−k r .x−ϕ 0 )
ψ 0 .e −k i .x = ψ 0 .e − x
δ
1
1
δ =
=
k i
˜
k
x x

ω k r
ω
v ϕ =
k r
 ω n = c v v c n λ = c ν = 2π.c ω n = A + B λ 2 A B v ϕ = λ ω c n

k = k r + j.k i ω

ω

c

2 = k 2 + ω c

c

2

 dx

k.xϕ ˜ 0)

ψ ˜ = ψ 0 .e j. ( ω t

k ˜ xϕ 0)

ψ ˜ = ψ 0 .e +j. ( ω.t

 ˜ k = f(ω)

 ˜ k r k i k = k r + j.k i

ψ ˜ = ψ 0 .e j. ( ω tk xϕ 0) = ψ 0 .e k i .x .e j.(ω.tk r .xϕ 0 )

˜

˜
A ˜ (ω) .e j.(ωt−k.x) dω
ψ = ∞
0
˜
A (ω)
ω 0 , k 0
ω
= ω 0 + u
∂k
u
k(ω) ≈ k 0 + ∂ω u = k 0 +
v
g
ω → u
˜
˜
g e j.(ω 0 t−k 0 x) du
ψ =
A (ω 0 + u) .e j. u t− u
v
−∞

 y y = y − 0 , t = y y = y + 0 T y y = y − 0 , t = T y y = y + 0 , t ∀t

, t t

Ox µ l

T 0

f f = λ. v

T (x, t) t x

x

2 y

∂t

2

τ = µ l

λ

+ =

τ ∂t

1 c

∂y

2 2 y

0 ∂x 2

c 0 = T 0

µ

l

l c V I

c 0 =

1

l.c

a = 1mm b = 3, 5mm ε r = 2, 26

 c 0 Z c

c = 2π.ε 0 r

ln (

a )

b

l = µ

2π ln a

0

b

c 0 = 2.10 8 m.s 1

l

c r 1 g 2

r 1 = 0 g 2 = 0

2 V

∂x 2

=

l.c 2 V

∂t 2

+ (r 1 .c + l.g 2 ) V

∂t

+ r 1 .g 2 .V (x, t)

˜

k 2 = ω 2

c

2

0

˜
˜
˜
∂ 2 ψ
∂ ψ
∂ 2 ψ
2
+ 1
= c
0
∂t 2
τ ∂t
∂x 2

˜

k 2 = ω

2

0 +

c

2

j.ω

τ.c

2

0

 ˜ ˜ ˜ ∂ 2 ψ l.c ∂ 2 ψ (r 1 .c + l.g 2 ) ∂ ∂t ψ = + ∂x 2 ∂t 2

˜

+ r 1 .g 2 . ψ

˜

k 2 = l.c.ω 2 + j. (r 1 .c + l.g 2 ) ω r 1 .g 2

M L K a

2 ψ

 + ω p .ψ = c 2 ∂ 2 ψ 2 ∂x 2 c 2 = a 2 .ω 2 ∂t 2 p

ω 2 = ω p + c 2 .k 2

2

ω 2 = ω p + k 2 .c 2

2

ω ω p c

 v ϕ v g

v g c v ϕ

c

v g = v c ϕ 2

h

ω 2 = g.k + γ.k 3 th (k.h)

µ

g = 9, 81m.s 2 µ = 1, 0kg/L γ = 72.10 3 SI

λ = 1000km h = 5km

 λ = 5m λ = 1cm

λ = 2cm h = 1mm

v g = 800km/h v g = 5km/h v g = 30cm.s 1 v g = 20cm.s 1

0, 1dB.km 1

I(z) = I 0 .e β.z I dB = 10.log L = 30km

I ref

I

0

10

ln(10) z

A(ω) =

A

ω

0

ω ω m ω ; ω m + ω A(ω) = 0

2

2

ψ(x, t) = A 0 .sinc ω

2

t

x g . cos (ω m .t k m .x)

v

A 0
(ω−ω m ) 2
√ 2.π.∆ω e
π β 2
e −α 2 .x 2 +j.β.x .dx = √
e
4.α 2
α
−∞
β α − π
+ π
4
4

A(ω) =

2.ω 2

ψ(x, t) = A 0 .e

(∆ω) 2

2

g 2

tx

v

. cos (ω m .t k m .x)

ω ω m

ψ(x, t) =

n=+ N1

2

n=N1

2

A 0 . cos (ω n .t k n .x)

ω n = ω m +

N n ω N

t

ω

ψ(x, t) = A 0 .

sin ω tx

g

2
v
∆ω
sin
2.N t− x
v
g

. cos (ω m .t k m .x)

λ

v g = v φ λ dv φ

ω = A.k α A α k

v φ α

v g = α.v φ

Z c x < x 0

 ˜ Z x = x 0

r V =

˜

ZZ Z c +

c

˜

Z

= r I

R =

|

ZZ c| 2

˜

| Z c +

Z | 2

˜

x = x 0

x < x 0 Z c 1

x > x 0 Z c 2

r I = Z c 1 Z c 2 = r V

Z c 1 +Z c 2

t I =

2.Z c 1

Z c 1

Z c 1 +Z c 2

Z

c

=

2 t V

2

R = ( Z c 1 Z c 2 ) 2 T =

( Z c 1 +Z c 2 )

4.Z c 1 .Z c 2

( Z c 1 +Z c 2 ) 2

µ 1 x < 0

µ 2 x > 0 T 0 x = 0

α = µ 2

µ 1

r˜ =

√ µ 1 − √ µ 2

µ 1 + µ 2

˜

t

=

2. √ µ 1

µ 1 + µ 2

dx a b

ε r = 2, 25 χ dx = 2.π.ε 0 .ε r dx λ dx =

ln (

a b )

c 0

µ

2ln

0

a b dx

c c c c

c

c c c

2/3c c

x x = 0 Z 1 x < 0 Z 2 x > 0 x = x 1 x = x 2 x = x 1 x = x 2